Assessing the Stability of Poor Drainage Soil Slopes Under the Combined Effect of Water Level Drawdown and Rainfall. Issue 4 (September 2019) - Tang, Libin; Wang, Ling; Zhang, Wengang
Abstract: In rainy season, the reservoir water level sometimes decreases greatly for the requirement of flood discharge. Such phenomenon may cause severe landslides for poor drainage soil slopes. Therefore, it's necessary to assess the slope stability under the combined effect of rainfall and water level drawdown. In this study, a homogeneous soil slope was modelled to investigate the relative importance and failure mechanism of water level drawdown and rainfall. Both the "factor of safety" (FOS) and the "probability of failure" (POF) were computed in the analysis. The numerical results show that landslides are more susceptible to water level drawdown, while rainfall is a secondary influence to poor drainage soil slopes, subjected to the combined effect of water level drawdown and rainfall.